Utility of in vitro interferon‐γ release assay in differential diagnosis between intestinal tuberculosis and Crohn's disease. Issue 2 (24th January 2013) - Lei, Yuan; Yi, Feng Ming; Zhao, Jie; Luckheeram, Rishi Vishal; Huang, Sha; Chen, Min; Huang, Mei Fang; Li, Jin; Zhou, Rui; Yang, Gui Fang; Xia, Bing
<x xml:space="preserve">Abstract</x> Objective To evaluate the diagnostic utility of interferon‐γ release assay (T‐SPOT.TB) for the differential diagnosis between Crohn's disease (CD) and intestinal tuberculosis (ITB). Methods A total of 103 CD and 88 ITB patients, confirmed by histology and anti‐tuberculosis treatment response from 2003 to 2011, were included. Their characteristics and clinical features were recorded. Mycobacterium tuberculosis (MTB) polymerase chain reaction (PCR) of IS6110, in vitro T‐SPOT.TB, tuberculin skin test (TST), immunoglobulin G (IgG) antibody to MTB (protein chip), serum anti‐Saccharomyces cerevisiae antibodies (ASCA IgG, chronic inflammatory bowel disease profile) and acid‐fast staining of biopsied colonic tissue specimens were performed. Statistical analysis was conducted to determine their concordance with the diagnosis and its sensitivity, specificity, positive (PPV) and negative predictive value (NPV). Results Abnormal pulmonary X‐ray, ascites and lesions of both cecum and ascending colon were more associated with ITB, while intestinal surgery and lesions of both ileum and adjacent colon were more commonly seen in CD. Significant diagnostic concordance was found using T‐SPOT.TB (κ = 0.786) by consistency test. The sensitivity, specificity, PPV and NPV of T‐SPOT.TB were 86%, 93%, 88% and 91%, respectively, and the sensitivity and NPV were significantly higher than other examinations (P < 0.05). Conclusion T‐SPOT.TB is a valuable assay in differentiating ITB from CD, particularly in the diagnostic exclusion of ITB based on its high specificity and NPV.